Inter- and Intra-Species Variation and Genetic Diversity of Flea Ectoparasites in Hedgehogs (Mammalia, Erinaceidae) Collected in Northern Algeria - Ourida Chebbah; Karim Souttou; Karim Ouachek; Mohamed Lounis; Sophie Brun; Arezki Izri; Mohammad Akhoundi (Insects)
Hedgehogs are small omnivorous mammals prevalent across Europe, Asia, and Africa. The expanding intrusion of humans into hedgehog habitats and rising popularity of keeping exotic animals like hedgehogs as pets have disrupted the delicate balance of the human–animal–environment interface. Despite their ecological importance, hedgehog-borne flea species have received limited research attention, with most studies focusing on their vectorial role, and except one report, nothing on the species composition and genetic diversity of hedgehog flea specimens. An inventory and phylogenetic investigation, conducted for the first time in Algeria as well as in North Africa, allowed for collecting 45 hedgehogs (15 males and 30 females) and 303 fleas, and analyzing them through morphological and molecular approaches. The hedgehog specimens were subjected to macro- and microscopic examinations based on diagnostic morphological criteria and morphometric measurements, resulting in their identification as Atelerix algirus. This study represents the first report of this species’ prevalence in Djelfa. The ecological and geographical diversity of the studied areas, from arid deserts to humid regions, highlights the adaptability and resilience of A. algirus to diverse habitats. Additionally, 271 and 32 flea specimens were morphologically identified as Archaeopsylla erinacei and Ctenocephalides felis, respectively. Molecular examination targeting ITS1-rDNA further confirmed the morphological identification of fleas species. Phylogenetic analysis of fleas’ ITS1-rDNA sequences revealed heterogeneity, with the specimens clustering into two distinct clades. The first clade comprised two populations of A. erinacei, while the second clade included C. felis specimens of this study, grouped with homologous sequences from various regions worldwide. No correlation between flea species and geographical locations was observed demonstrating the sympatric distribution of flea specimens in the studied regions. In addition, no hybrid or genetic combination notion was observed among the flea specimens processed in this study compared with those coming from other countries. These findings contribute to our understanding of the species composition and distribution of hedgehogs and their flea ectoparasites in Algeria and provide a baseline for future epidemiological and entomological research in the country.